Gingivostomatitis herpetik primer pada anak Primary herpetic gingivostomatitis on children - Astrid Palmasari; M. Jusri (Journal of Dentomaxillofacial Science, 2012)
Herpetic gingivostomatitis is an infection of primary herpes simplex virus (HSV) type-1 characterized byvesiculoulcerative lesion. This diseasae commonly seen in 1 until 5-year-old children, but occur in adultoccasionally. This paper reports a 5-year-old girl with chief complaint ulcerations in oral cavity. Fever and malaiseproceed ulcers five days before. The diagnosis primary herpetic gingivostomatitis was based on this first and manyulcers. Antivirus agent, multivitamin, benzydamine HCl gargle and high calorie and high protein diet was given tothe patient. Herpetic gingivostomatitis usually healed by time, but recurrent herpes simplex virus can avoid withproper therapy and monitoring.